THE INFLUENCE OF KNOWLEDGE, BENEFITS AND CONVENIENCE ON USERS OF QUICK RESPONSE CODE INDONESIA STANDARD (QRIS) AT BANK SYARIAH INDONESIA (BSI) MOBILE - Meliza, Meliza; Ismuadi, Ismuadi; Mulia, Rika (Universitas Syiah Kuala, 2024)
The use of physical money is currently being replaced by electronic money. Indonesia is one of the countries that has started using electronic money for transactions. One of the electronic payment methods used by the Indonesian public is QRIS BSI mobile. QRIS is a facility that allows cashless transactions. This quantitative research aims to determine the influence of Knowledge, Benefits, and Ease of Use on the Decision to Use QRIS on BSI mobile among students. This study uses primary data obtained through the distribution of questionnaires via Google Forms. The population of this research consists of students from the 2023 cohort at UIN Ar-Raniry Banda Aceh. The sampling technique used is Purposive Sampling and Proportionate Stratified Random Sampling. The analysis tool used is SPSS Version 26. The results of this study indicate that Knowledge, Benefits, and Ease of Use have a positive and significant effect on the Decision to Use QRIS on BSI mobile among students. The Ease of Use variable has the most dominant influence on the Decision to Use.